1999
DOI: 10.1093/jn/129.5.1045
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Atrophy Has a Greater Impact on Nitrogen Metabolism than Liver By-Pass in Piglets Fed Identical Diets via Gastric, Central Venous or Portal Venous Routes

Abstract: Whole-body nitrogen metabolism is altered during parenteral feeding as a result of gut atrophy and/or lack of splanchnic first-pass metabolism. We developed in vivo models to describe the metabolic and physiologic effects of first-pass metabolism by the small intestine/liver, liver or non-splanchnic tissues. Fifteen 2- to 4-d-old piglets were fed identical diets continuously for 8 d via gastric (IG), portal (IP) or central venous (IV) catheters. Despite similar weight gain, IV and IP pigs had higher nitrogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…It has been postulated in chickens that efficient utilization of dietary protein and relatively low levels of amino acids in the plasma are fairly closely related (Hewitt and Lewis, 1972), and reduced plasma amino acids with amino acid supplementation is due to improved amino acid balance which stimulated rate of weight gain and caused removal of amino acids for protein synthesis. Studies with young pigs (Bertolo et al, 1999) also support the supposition that higher protein synthesis rates result in lower free amino acid concentrations for several essential amino acids. Nieto et al (1994) studied the effect of supplementation a soyabean meal diet with DL-methionine on fractional rates of protein synthesis and degradation in the skeletal muscle and liver of growing chickens.…”
Section: Methods Of Samplingmentioning
confidence: 71%
“…It has been postulated in chickens that efficient utilization of dietary protein and relatively low levels of amino acids in the plasma are fairly closely related (Hewitt and Lewis, 1972), and reduced plasma amino acids with amino acid supplementation is due to improved amino acid balance which stimulated rate of weight gain and caused removal of amino acids for protein synthesis. Studies with young pigs (Bertolo et al, 1999) also support the supposition that higher protein synthesis rates result in lower free amino acid concentrations for several essential amino acids. Nieto et al (1994) studied the effect of supplementation a soyabean meal diet with DL-methionine on fractional rates of protein synthesis and degradation in the skeletal muscle and liver of growing chickens.…”
Section: Methods Of Samplingmentioning
confidence: 71%
“…The reasons for the discrepancies remain unknown, but might be attributable to two reasons: (1) The lipid content of the intestine (18.7%) is higher than muscle (12.0%) in carp, which indicated that fish intestine is more susceptible to oxidative damage than muscle [61]. Moreover, a study in rats demonstrated that the intestine was one of the most important organs involved in arginine metabolism and was primarily affected in arginine deficiency relative to muscle [24]. Hence, intestine could compensate to improve antioxidant enzyme activities when dietary arginine is deficient.…”
Section: Arginine Regulated the Intestinal Antioxidant Capacity Via Nmentioning
confidence: 99%
“…However, studies have not addressed the effect of arginine on TJ mRNA expression in fish intestine. In rats, a study showed that dietary arginine deficiency disrupted tight junction proteins in the intestine [24]. The above information indicated that arginine may have an effect on fish intestinal TJs.…”
Section: Introductionmentioning
confidence: 95%
“…In parenteral feeding, nutrients infused into a central vein bypass exclusive first-pass metabolism by the intestine and liver; these nutrients are therefore provided to nonsplanchnic organs in concentrations that are not modified by first-pass splanchnic metabolism. In piglets fed complete diets via a central or portal vein, we have previously shown that both routes of feeding led to extensive gut atrophy, and hence lowered intestinal metabolic capacity (4). These studies also demonstrated that in parenterally fed piglets, gut atrophy has a greater impact on nitrogen metabolism than bypass of first-pass liver metabolism (4,5).…”
mentioning
confidence: 91%
“…In piglets fed complete diets via a central or portal vein, we have previously shown that both routes of feeding led to extensive gut atrophy, and hence lowered intestinal metabolic capacity (4). These studies also demonstrated that in parenterally fed piglets, gut atrophy has a greater impact on nitrogen metabolism than bypass of first-pass liver metabolism (4,5). In support of this conclusion, other investigators have also shown that approximately one third of the dietary indispensable amino acids is consumed by the healthy intestine on first pass alone (6).…”
mentioning
confidence: 99%